Hypoxic Training Ameliorates Skeletal Muscle Microcirculation Vascular Function in a Sirt3-Dependent Manner - Ma, Chunwei; Zhao, Yongcai; Ding, Xiaoqing; Gao, Binghong (Frontiers in Physiology, 2022)
Hypoxic training improves the microcirculation function of human skeletal muscle, but its mechanism is still unclear. Silent information regulator 2 homolog 3 (Sirt3) can improve mitochondrial function and oxidative status. We aimed to examine the role of Sirt3 in the process of hypoxic training, which affects skeletal muscle microcirculation. C57BL/6 mice were assigned to control (C), hypoxic training (HT), Sirt3 inhibitor 3-(1H-1,2,3-triazol-4-yl) pyridine (3-TYP), and 3-TYP + hypoxic training (3-TYP+HT) groups (n=6/group). Sirt3 inhibition was induced by intraperitoneal injection of Sirt3 inhibitor 3-TYP. After 6 weeks of intervention, microcirculatory capillary formation and vasomotor capacity were evaluated using immunofluorescence, Western blot, biochemical tests, and transmission electron microscopy (TEM). Laser Doppler flowmetry was used to evaluate skeletal muscle microcirculation blood flow characteristics. Six weeks of hypoxic training enhanced skeletal muscle microcirculation function and increased microcirculatory vasodilation capacity and capillary formation. After the pharmacological inhibition of Sirt3, the reserve capacity of skeletal muscle microcirculation was reduced to varying degrees. After the inhibition of Sirt3, mice completed the same hypoxic training, and we failed to observe the microcirculation function adaptation like that observed in hypoxic training alone. The microcirculation vasodilation and the capillaries number did not improve. Hypoxic training improved skeletal muscle microcirculation vasodilation capacity and increased skeletal muscle microcirculation capillary density. Sirt3 is involved in the adaptation of skeletal muscle microcirculation induced by hypoxic training.